(untitled) (Texas Journal of Medical Science, 2025)
In recent years, the consumption of energy drinks has become increasingly popular among young adults, especially university students. These beverages are commonly used to combat fatigue, improve concentration, and enhance academic performance. However, numerous studies have reported potential adverse cardiovascular effects associated with excessive energy drink consumption, including hypertension, arrhythmias, and endothelial dysfunction. Medical students represent a particularly vulnerable group due to high academic pressure, irregular sleep patterns, and frequent caffeine use.